Weight-specific Morbidity and Mortality Rates among Low Birthweight Infants in Two Developing Countries (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Summary Objective: The objective was to compare the morbidity and mortality data among low birthweight (LBW) infants in two developing countries with different medical facilities, and determine where further improvements are possible, Methods: Data were extracted from the admission records and case notes of neonates with birthweight <2500grams, admitted to Qatif Central Hospital (QCH), Saudi Arabia, from January 1990 to December 1994, and those of corresponding neonates admitted to the Wesley Guild Hospital (WGH), Ilesa, Nigeria from January 1991 to December 1995. The data obtained were analysed retrospectively. Outcome Measures: Comparison of birthweight-specific and gestational age-specific mortality rates among LBW infants delivered at Wesley Guild Hospital (WGH), Ilesa and Qatif Central Hospital (QCH), Qatif, Saudi Arabia. Results: When the data on 368 infants from each hospital were compared, the commonest factors found to be associated with mortality rate were respiratory distress syndrome in QCH and birth asphyxia in WGH. The proportions of infants of VLBW (BW <1500gm) and GA< 32 weeks were higher in QCH than WGH (p<0.001). The overall mortality rate was higher in WGH than in QCH although the difference was not significant (p>0.1). The mortality rate was significantly higher among the VLBW group in WGH than in QCH (p <0.001). Conclusions: The neonatal mortality rates in the LBW infants in both units were still very high. Improvement in access to antenatal care should reduce LBW rates and associated morbidity and mortality in both hospitals, while the introduction of neonatal intensive care facilities in WGH should greatly reduce the high mortality rate among VLBW infants. Keywords: Low birth weight, very low birthweight, respiratory distress syndrome, morbidity and mortality, neonatal units, developing countries.